Beach colors - Noble, Shelley (William Morrow, 2012)
While renowned designer Margaux Sullivan was presenting her highly praised collection during New York City's Fashion Week, her husband was cleaning out their bank account. A week after he disappeared, the bank foreclosed on Margaux's apartment and business. She returns to the small coastal town of Crescent Cove, Connecticut, where she once knew love, joy, and family before she put them behind her on the climb to fame. Margaux is soon rediscovering the beauty of the shore ... and finding a forgotten place in her heart that wants to love again ...